DIRECTING FOR "BAYANG KU, BAYANG MU" SHORT FILM - Arsyad, Viqi Zuldan Arlyandi; Al Ansory, Muchammad Zaenal; Barlian, Yelly Andriani (eProceedings of Art & Design, 2024)
Since the Covid 19 virus spread around the world in 2020, the virus has affected almost every aspect of people's lives in Indonesia. From the economy, society, and education. Students are taking online classes without knowing when they will come back to school or college. Many students became detached from society and had social withdrawal. This research aims to explore the phenomenon of social isolation caused by the COVID-19 pandemic, especially in teenagers and young adults and how this phenomenon can be used as a basis for developing a short film as a final project. Through a several data collection method such as literature review, observations, questionnaires and analysis from the references of several similar works, this research seeks to identify that the pandemic has caused drastic changes in teenagers and young adult social lives, with restrictions such as lockdowns and social distancing triggering self-isolation and deep feelings of loneliness. Based on the data that will be obtained, the author intends to produce a short film that depicts in detail the emotional experiences of teenagers and young adults during social isolation, exploring feelings of loneliness, worries about the future, and their efforts to find human connections in difficult situations. Keywords: adolescent, loneliness, self isolation, short film, social life